1975
DOI: 10.1111/j.1432-1033.1975.tb02481.x
|View full text |Cite
|
Sign up to set email alerts
|

d‐Glucose‐6‐Phosphate Dehydrogenase (Entner‐Doudoroff Enzyme) from Pseudomonas fluorescens

Abstract: 1. The existence of two different ~-glucose-6-phosphate dehydrogenases in Pseudomonas Juorescens has been demonstrated. Based on their different specificity and their different metabolic regulation one enzyme is appointed to the Entner-Doudoroff pathway and the other to the hexose monophosphate pathway.2. A procedure is described for the isolation of that ~-glucose-6-phosphate dehydrogenase which forms part of the Entner-Doudoroff pathway (Entner-Doudoroff enzyme). A 950-fold purification was achieved with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1
2

Year Published

1979
1979
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 79 publications
2
34
1
2
Order By: Relevance
“…These data indicate that Zwf-2 is active even when the energy status of the cell is good, probably taking part in the pentose phosphate pathway operating in the anabolic direction. Lessmann et al (5) reported that the most highly expressed isoenzyme, now annotated as Zwf-1, showed a slight preference for NAD ϩ (5), while our results indicate that both enzymes prefer NADP ϩ to NAD ϩ as a cofactor. The reasons for this discrepancy are not known but could, for instance, be due to strain-dependent differences.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…These data indicate that Zwf-2 is active even when the energy status of the cell is good, probably taking part in the pentose phosphate pathway operating in the anabolic direction. Lessmann et al (5) reported that the most highly expressed isoenzyme, now annotated as Zwf-1, showed a slight preference for NAD ϩ (5), while our results indicate that both enzymes prefer NADP ϩ to NAD ϩ as a cofactor. The reasons for this discrepancy are not known but could, for instance, be due to strain-dependent differences.…”
Section: Resultscontrasting
confidence: 56%
“…We wanted to study the contributions of glucose dehydrogenase (Gcd) and glucose-6-phosphate dehydrogenase (G6PDH; also called Zwf) to these processes. Lessmann et al (5) have described two different G6PDHs from P. fluorescens and have shown that the activity of one of these isoenzymes did not vary much with the carbon sources tested, while the other was induced by glucose (5). It is not clear, however, whether the two P. fluorescens Zwf enzymes have strictly defined roles, one being catabolic and the other anabolic, or if either one would be sufficient for growth.…”
mentioning
confidence: 97%
“…U14553). While P. fluorescens and Pseudomonas cepacia (reclassified as Burkholderia cepacia) have two glucose-6-phosphate dehydrogenases that function with either NAD ϩ (in a catabolic role) or NADP ϩ (in an anabolic role) (7,20,25), it is clear that P. aeruginosa has a single glucose-6-phosphate dehydrogenase activity (Zwf) capable of using either NAD ϩ or NADP ϩ (22,28). One interpretation consistent with a single zwf gene is that the open reading frame with homology to devB/SOL represents a 6-phosphogluconolactonase.…”
Section: Resultsmentioning
confidence: 99%
“…Since this major flux change was not accompanied by any change in PP pathway or glycolytic transcript levels, PP pathway activity was not controlled at the transcriptional level as was suggested before (Blenke et al, 2003). Enzyme level control of this flux may be realized through the feedback inhibition of glucose-6-P dehydrogenase by NADPH known in other bacteria (Lessmann et al, 1975;Moritz et al, 2000). In this context, the inverted expression trends of the NADH-dependent, glycolytic GapA and the NADPH-dependent, gluconeogenic GapB isoenzymes (Fillinger et al, 2000) may be relevant.…”
Section: Discussionmentioning
confidence: 91%